The Beginnings of Cistercian Expansion in England: The Socio-Historical Context of the Foundation of Rievaulx (1132) - Burton, Pierre-André (Cistercian studies quarterly, 2007)
The article focuses on the expansion of the Cistercian reform in England. Its spread in the region owes much to the influence and the personal charisma of the founder and first abbot of Clairvux, Bernard. The author considers the foundation of Rievaulx, the first English daughter house of Clairvaux, to see how Bernard intervened. The foundation of Cistercian is classified in terms of the work of stabilization and pacification carried out the by Anglo-Norman faces.